Global Pandemic and Entrepreneurial Intention: How Adversity Leads To Entrepreneurship. (September 2022) - Usman, Magaji Abdullahi; Sun, Xinbo
The COVID-19 global pandemic eruption has thrown schedules, preferences, and current networks into disarray, creating inherent uncertainty about what lies ahead. This adversity brought on by covid 19 global pandemic created a displacement event in an individual life that can trigger sudden behavioral changes in an individual that would necessitate the search for several opportunities for making ends meet. However, individuals' responses to the occurrence of any particular event are influenced by their judgments of whether the event is negative or positive, as well as whether the occurrence of that event can be used to generate income. Thus this study is intended to explore how adversity leads to entrepreneurship during covid 19 global pandemic. Specifically, what can inspire individuals to start a new venture in today's world that has been severely impacted by the covid 19 global pandemic? This study collects survey data from popular cities in China and analyzed the data using a structural equation model to empirically explore what determines entrepreneurial intention to start a new venture during a global pandemic. The findings show that possible feasibility and necessity have a strong influence on entrepreneurial intention in starting a new venture.